Bioecological study and health status of barramundi (Lates calcarifer) in floating net cages at Loskala, Lhokseumawe - Anis Nugrahawati; Rinaldi Rinaldi; Asih Makarti Muktitama; Salmarika Salmarika; Akmal Izwar (Universitas Malikussaleh, 2026)
The cultivation of white snapper (Lates calcarifer) holds significant economic and ecological potential. This research was conducted at the Loskala Floating Net Cage (FNC) in Lhokseumawe City. The study aims to describe the ecological conditions of the waters and analyze the health profile of white snapper. The method applied was purposive random sampling at three sampling stations. The bioecological assessment indicates that water parameters are generally suitable for white snapper cultivation; however, elevated temperatures, dissolved oxygen levels approaching the minimum threshold, and biological oxygen demand (BOD) exceeding the standard at several stations have the potential to trigger eutrophication. These conditions correlate with the detection of Vibrio parahaemolyticus and Vibrio alginolyticus, which indicate risks to fish health as well as food safety. Keyword: Barramundi, Bioecological; Biological Oxygen Demand; Dissolved Oxygen; Floating Net Cages